Healthcare interpreting policy in China: Challenges, rationales, and implications - Wang, Wanhong (The Journal of Specialised Translation, 2023)
Unlike countries that have a long immigration history, China began to welcome a growing number of foreign residents since its opening-up in the 1970s. According to China’s latest census in 2021, about 1 million registered foreigners are staying and residing in China. This study investigates the policies and practices of healthcare interpreting services that support the language needs of foreigners in accessing healthcare in China. On this basis, it looks into the beliefs that governmental authorities and healthcare institutions may hold towards healthcare interpreting. It thus argues that healthcare interpreting in China is still in its preliminary stage, its implementation being patchy and consisting mainly of ad hoc healthcare interpreting. Healthcare interpreting management is indeed rarely overseen at the national, provincial, local, and institutional levels. Overall, as a crucial way to secure health rights, healthcare interpreting has not gained enough attention in China. The profit-driven model applied in the management of some hospitals and the foreign language education policy are both identified as factors influencing healthcare interpreting policy in China.